Urban–Rural Disparities in Metabolic Risk Factors for Hypertension Among the Elderly in Indonesia - Nugraha, Susiana; Wulandari, Puri (Kesmas, 2026)
Hypertension remains a major public health challenge among the elderly in low- and middle-income countries. This cross-sectional study examined demographic and metabolic factors associated with hypertension among the elderly living in urban and rural areas of West and Central Java Provinces, Indonesia. This study included 1,920 adults aged ≥60 years who had resided in the study areas for at least six months, were able to communicate effectively, and provided informed consent. Data were collected between March and August 2023 using stratified multistage random sampling, structured questionnaires, and biochemical measurements. Multivariable logistic regression revealed distinct patterns of association across settings. In urban areas, hypertension was associated with older age (AOR =1.366; 95% CI: 1.043–1.789), female sex (AOR=1.681;95% CI: 1.198–2.359), central obesity based on waist circumference (AOR=2.031; 95% CI:1.477–2.793), and abnormal blood glucose levels (AOR=2.821; 95% CI: 1.754–4.536). In rural areas, hypertension was associated with older age (AOR=1.613; 95% CI: 1.228–2.119), lower education level (AOR=0.686; 95%CI:0.507–0.928), central obesity (AOR = 1.613; 95% CI: 1.204–2.161), and blood glucose levels (AOR=1.503; 95% CI: 0.978–2.310). These findings highlighted that while metabolic markers, such as waist circumference and blood glucose, were universal predictors, demographic factors, such as sex and education level, varied by environment. Consequently, public health interventions must adopt tailored, context-specific approaches to manage hypertension in urban and rural Indonesian communities effectively.